Pole placement with minimum gain and sparse static feedback - Sevinov Jasur; Kadirov Yorkin; Boeva Okila; Boybutaev Sanjar; Rasulov Abdikhoshim (E3S Web of Conferences, 2024)
The work addresses the issue of developing polar positioning algorithms for linear control systems with despotic thinning constraints on a static feedback matrix. The design of sparse-limiting feedback control systems is considered to be one of the more complex issues, but the issue of defining the sparse feedback matrix, which allows the selection of eigenvalues or, in other words, the placement of poles, has not been fully studied. Algorithms for determining the eigenvalues, i.e., solving the problem of pole placement and finding the optimal solution of the technological process control system are considered in the work. The results of numerical analysis confirmed the effectiveness of these algorithms, which allows them to be used in solving practical problems of synthesizing adaptive control systems for technological objects.